Program "Freely Talking", based on the Communicative Approach to re-duce anxiety when speaking, in students of Quirihuac school, 2020 (SCIÉNDO INGENIUM, 2022)
The present research work seeks to determine the influence of the "freely talking" program, based on the communicative approach, in the reduction of anxiety when speaking, in students of Quirihuac school, 2020. In the development of the research, it was sought to find the level of anxiety, before and after the application of the educational program. The population for the investigation was 57 students of the fifth grade of secondary education and for the sample the fifth grade "b" of the same institution was selected, constituted by 28 students, 16 are women and 12 men between 15 and 16 years old. As a methodology, the pre-experimental design applied to a single evaluation group has been used. To measure the level of anxiety, the FLCAS instrument was applied. It has been concluded that the Freely Talking Program significantly reduces anxiety levels, observing that for the Pre-test 50% are located at the high level, 35.71% at the medium level and 14.29% at the low level. In the Post-test, the results change as a result of the "freely talking" program, which reduced anxiety levels, with 50.0% at the low level, 32.14% at the medium level and 17.86% at the high level.
Keywords: Foreign language; communicative apprehension; anxiety; negative attitudes; Freely Talking program